UNINTELLIGIBLE SPEECH: LISTENERS' AWARENESS TO INDONESIAN-ACCENTED SPEECH WITH PRONUNCIATION ERRORS - Syifa' Khuriyatuz Zahro (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2021)
There have been widely exposed researches that analyze accented and intelligible speech of foreign language; yet, the study concerning listeners' awareness of the pronunciation errors is hardly found. Therefore, the current study aims to find out segmental features and the source of errors that have caused unintelligible speech of Indonesian-accented speech and describe the listeners' awareness of the errors. This descriptive qualitative research investigates listeners' transcripts of Indonesian-accented speeches through purposive sampling. The standard orthography transcripts are then transformed into phonemic transcripts. They are analyzed by error analysis based on phonological operation by Davenport and Hannahs. The result is further checked by the listeners to generate their awareness of the errors through interviews. There are consonants causing unintelligibility more than vowels. Furthermore, it is found that there are six pronunciation features affecting listeners' awareness of speakers' pronunciation errors:  1) aspiration, 2) spelling system, 3) blended phonemes, 4) absent phonemes, 5) different articulation, and 6) homophone in the research.